PENGARUH HASIL BELAJAR METODOLOGI PENELITIANTERHADAP PENYELESAIAN PROPOSAL SKRIPSI (STUDI KASUS: MAHASISWA PENDIDIKAN TEKNIK BANGUNAN FT UNP SEMESTER JULI-DESEMBER 2017) - 2087-2090, Fuji Asema (CIVED, 2018)
Abstract—The main of this research is about students who got good of Methodology Research course`s, but the completion of thesis proposal was not already. Therefore, should be known what the effect of learning results of Research Methodology toward completion of thesis proposal, student of PTB FT UNP semester July-December 2017. The population of this research is 153 students who taked thesis proposal semester July-December 2017. The sample is 61 students who taked thesis proposal semester July-December 2017. Random technique was used by the sample research. The data were primary and secondary data. The primary data was obtained by questionnaires that they distributed to the respondents, the secondary data was the value of Research Methodology.The results showed there was an effect from the learning result of Research Methodology on completion of thesis proposal. Therefore headmaster of PTB conclude the value of Research Metodology as recommendation to allow the student creating thesis proposal with B point.Keywords: Research Metodhology, Thesis, Learning Result